The Portrait of Hijrah in the Novel Assalamualaikum Beijing by Asma Nadia and Kukejar Cinta ke Negeri Cina by Ninit Yunita - Deri Rachmad Pratama; Yasir Riady; Wilda Sueree (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2024)
This study examines the phenomenon in novels with an intertextual approach. The focus of the research is the portrait of hijrah in the novel Assalamualaikum Beijing and the novel Kukejar Cinta ke China. In addition, religious and cultural values as well as hypogram and transformation relationships. The data of this research is in the form of dialogues or narratives that contain structural elements, religious values, and culture. Data collection techniques are carried out by document analysis and interviews. Data validation is carried out by theoretical triangulation. Data analysis is based on the Miles and Huberman model which consists of three analysis activities, namely: data reduction, data display, and conclusion or verification. The theme of these two novels is hijrah as a process of finding true love. The meaning of hijrah in this context is a change in the character of the character to become a nobler person before being met with a soul mate. All of this is illustrated in the characterization of Asma and Zhongwen in Assalamualaikum Beijing and Imam and Widya in Kukejar Cinta ke China. The novel Kukejar Cinta ke China as a transformation continues its hypogram because of the many similarities found in the two novels, both structurally and in terms of religious and cultural values. The inspiration  for the novel Assalamualaikum Beijing began with Asma's trip to Beijing before the Olympics, while Ninit Yunita got the idea to write the novel Kukejar Cinta ke Negeri China during the Hajj pilgrimage in 2003. Thus, the transformation deviates from the hippogram if studied expressively.